2016
DOI: 10.1080/15367967.2016.1161517
|View full text |Cite
|
Sign up to set email alerts
|

Where did the reference desk go? Transforming staff and space to meet user needs

Abstract: A sharp decline in the number of reference queries prompted the library administration at Indiana State University to begin a project to combine the circulation, reference, and IT desks to reduce staffing at a new consolidated service point. All faculty and staff in the reference/instruction and circulation units participated in the project. The new arrangement and subsequent removal of librarians from routine desk duties have expanded instructional opportunities, consistent with the university's goals. Projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In light of declining reference transactions at our institution, and supported by the literature (Bunnett et al, 2016;Coleman, Mallon & Lo, 2016;Stevens, 2013;Applegate, 2008), senior library assistants and MLIS students began to serve shifts on the reference desk. While there was consensus that it was important to maintain reference service hours, we decided that librarians did not need to provide all the frontline service.…”
Section: Referencementioning
confidence: 99%
“…In light of declining reference transactions at our institution, and supported by the literature (Bunnett et al, 2016;Coleman, Mallon & Lo, 2016;Stevens, 2013;Applegate, 2008), senior library assistants and MLIS students began to serve shifts on the reference desk. While there was consensus that it was important to maintain reference service hours, we decided that librarians did not need to provide all the frontline service.…”
Section: Referencementioning
confidence: 99%
“…Bunnett et al employed a methodical approach to reduce and ultimately eliminate the dedicated presence of librarians at service desks at Indiana State University after seeing a 45 percent reduction in reference interactions over five years. 6 They found that the consolidation of desks led to increased instructional opportunities for librarians at the institution. LaMagna, Hartman-Caverly, and Marchetti also outline the implementation process for a tiered or triage reference model.…”
Section: Value Of Referencementioning
confidence: 99%
“…The Association of College and Research Libraries (ACRL) statistics for libraries in universities with doctorate degrees indicate that across the United States, the number of reference transactions declined from 21.3 million in 2001 to just nine million in 2012, a drop of 57% (Bunnett et al, 2016). UND is a public research university with an enrollment of over 13,000 students in 2019.…”
Section: Purpose and Process Of The Prc Programmentioning
confidence: 99%